Effects of dual task training on gait temporal-spatial parameters of children with autism - Souza, Felipe Heylan Nogueira de; Lisboa, Ana Karoline Pordeus; Maia, Maria De Fátima Targino; Santos, Mikaelle Rossane Duarte Dos; Filho, Edson Meneses da Silva; Cezarino, Leandro Gonçalves; Cacho, Roberta de Oliveira; Cacho, Ênio Walker Azevedo (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Autism Spectrum Disorder (ASD) is neurological conditions typically identified in early childhood. Children with ASD mainly suffer from incapacities in communication and social interaction, in addition to exhibiting unusual patterns of behavior. Objective: The present study aimed to evaluate the effects of the dual task training in the temporal-spatial aspects of gait in children with ASD. Method: It is a series of case which used as assessments the Childhood Autism Rating Scale (CARS), Motor Function Measurement, Tinetti Index and Plantigraphy. The incremental treadmill test was used previously to establish the appropriate velocity of each subject for the accomplishment of the double task protocol. Initially a warm-up of three minutes was done at three km/h, then increments of 1 km/h were performed every three minutes and the maximum speed was obtained when the individual reached the speed limit of their ambulation. All subjects underwent an experimental protocol consisting of performing dual task activities on an Embreex 552® treadmill for four weeks, twice a week on alternate days and each activity lasted three minutes. Results: The sample consisted of 6 individuals. The pre- and post-test values for gait and balance, evaluated using the Tinetti Index, was 23.33 (± 2.87) for the pre-test and 24.16 (± 1.72) for the post-test with no statistical significance (p = 0.317). The types of foot of the sample were 50% flat feet, 25% high arches feet and 25% neutral feet. The axial and proximal motor function presented statistical difference in the intragroup analysis (p = 0.008). Conclusion: The protocol was not sufficient to verify improvements in the gait of children with autism.